Synthesis , Characterization and Study The Liquid Crystalline Properties of N-Acyl , Thiourea and Imidazole Derivatrives. - Tomma, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The synthesis , characterization and mesomorphic behaviour of new Nacyl , thiourea and imidazole derivatives which derived from corresponding Schiff bases are reported. All the synthesized compounds which contain flexible methylene group in the centre of the molecule did not show any liquid crystalline properties . The derivatives of N- acyl [III]e and thiourea [VI]e which contain biphenyl and all compounds with one phenyl in the centre of the molecule display liquid crystalline behaviour .While the imidazoles did not show any liquid crystalline properties except [V]b [V]e with biphenyl in the centre of the molecule . All the synthesized liquid crystals have a high transition temperature and a wide range of thermal stability